Emergence of a blaNDM-5-carrying extensively drug-resistant Enterobacter cloacae ST1718 in Saudi Arabia: Insights from comprehensive genome analysis - Ibrahim A. Al-Zahrani; Thamer M. Brek (Journal of Infection and Public Health)
Background: Patients with severe COVID-19 may require intensive care unit (ICU) admission to manage life-threatening complications. However, ICU admission is associated with an increased risk of acquiring nosocomial infections caused by multidrug-resistant (MDR) bacteria, particularly carbapenem-resistant Enterobacterale (CRE). Enterobacter cloacae complex (ECC), a group of closely related species including Enterobacter cloacae, is a common cause of healthcare-associated infections (HAIs). Methods: The study conducted a comprehensive genomic analysis of an extensively drug-resistant (XDR) E. cloacae strain (ECloa-JZ71) isolated from the blood of a critically ill COVID-19 patient in Jazan, Saudi Arabia. Results: ECloa-JZ71 exhibited resistance to multiple antimicrobial agents, except for amikacin, gentamycin, and fosfomycin. Whole-genome sequencing revealed that ECloa-JZ71 had a rarely reported sequence type, ST1718. Resistance to β-lactam antibiotics was primarily mediated by the genes blaCMH-3, blaTEM-1B, blaLAP-2, and blaNDM-5. The strain was found to harbor IncFIB(pECLA) and IncX3 plasmid replicons, with the latter encoding the blaNDM-5 gene. The IncX3 plasmid was identified as a significant contributor to the dissemination of the blaNDM-5 gene among Enterobacterale species The coexistence of blaNDM-5 and other carbapenem-hydrolyzing enzymes explains the reduced efficacy of β-lactam drugs in ECloa-JZ71. The coexistence of blaNDM-5 and other carbapenem-hydrolyzing enzymes explains the reduced efficacy of β-lactam drugs in ECloa-JZ71. The presence of specific virulence factors along with carbapenem resistance in ECloa-JZ71 may enhance its pathogenesis, complicating treatment and control efforts. Conclusion: The findings highlight the need for monitoring the spread of multidrug-resistant clones, conducting molecular epidemiological studies, and implementing effective infection control measures to prevent the dissemination of antimicrobial resistance in healthcare settings.